Spiritual Well-Being of Nursing Students - Elizabeth Fajardo Ramos (Universidad de Alicante, 2019)
Objective: To determine the spiritual wellbeing (BE) of nursing students in a public university in the department of Tolima, Colombia. Method: Quantitative, descriptive, exploratory, cross-sectional study. Sampling at convenience constituted by 264 nursing students of a higher education institution of the city of Ibague-Tolima, to whom the instrument SHALOM-3 was applied, to measure the spiritual well-being (dissonance and harmony) in the personal domains, transcendental, environmental and communal. Results: The sample was constituted by women in 63.6% (168), singles 90% (238) and 65% (172) with ages between 16 and 21 years, of catholic religion 66.5% (175), with high Percentages in the levels of harmony between the domains, It is emphasized that the strategies that promote spiritual well-being in the students were the family, being happy, time to relax, music and spirituality in life. Conclusion: These findings could be used to lay the foundations for greater support in promoting the spiritual well-being of nursing students in areas in which they presented dissonance.